Design and development of an automated metered dose inhaler (MDI) for asthmatic patient - Tsen, Vui Hin (2018)
To date, infant with illness associated with the pulmonary airway is treated by a doctor using a spacer device with metered dose inhaler (MDI) to allow the infant to breathe in the medication known as salbutamol. Current asthma spacer does not provide systematic way of monitoring and displaying the percentage value of the propellant. Furthermore, user non-compliance is found to contribute towards longer recovery rate. Therefore, this product is designed and developed capable of detecting the propellant level inhaled by the infant by using a MQ-6 gas sensor and monitoring its percentage value. The display of available puffs of MDI canister and the battery indicator for the system are also included in the device. The automated actuation MDI was required a push button to press the MDI canister where this project utilised Arduino Nano as the microcontroller to control the system operation and all the reading values will be displayed on the OLED. RGB LED is also used to visualise the propellant level. The obtained results of the detection of propellant in voltage from the MQ-6 gas sensors were analysed in MATLAB to make comparison through the obtained results. Without propellant, voltage recorded is 0.640±0.024V whereas high concentration of propellant displayed voltage of 1.126±0.020V. The mean standard error rate of propellant detection is 5.584%. The first design of the actuation device and interface monitoring display of automated MDI were recorded the highest percentage which is 75% and 80%. The concentration of propellant depends on the ambient temperature due to the MQ-6 gas sensor required minimum working temperature between 20oC to 22oC. The mean weight of the MDI canister for each puff is 6.257mg and the standard deviation is 3.629mg. Due to experiment conducted, the speed and pressure of pressing MDI canister causes variability in the released of salbutamol and propellant. Observation proved that ambient temperature and propellant released amount also influenced the final reading from the automated actuation MDI.